Pseudocyst and a Collar Stud Abscess: New Face of Necrotizing Enterocolitis - Kumar, Hemant; Patel, Ramnik; Patwardhan, Nitin; More, Bharat (Journal of Neonatal Surgery, 2014)
Meconium pseudocyst formation secondary to antenatal perforation is well described. We present a preterm infant who had intra-abdominal pseudocyst formation following postnatal intestinal perforation secondary to necrotizing enterocolitis (NEC) and secondarily leading to extra-abdominal collar stud abscess. This is new face of NEC and this presentation has not been reported earlier.